2010
DOI: 10.1111/j.1365-2044.2010.06263.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring sedation in the critically ill child

Abstract: SummarySedation is an essential part of the management of the critically ill child, and its monitoring must be individualised and continuous in order to adjust drug doses according to the clinical state. There is no ideal method for evaluating sedation in the critically ill child. Haemodynamic variables have not been found to be useful. Clinical scales are useful when sedation is moderate, but are limited by their subjective nature, the use of stimuli, and the impossibility of evaluating profoundly sedated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
0
15
0
2
Order By: Relevance
“…To date, the most comprehensive review examining the uses and limitations of BIS, MLAEP, and several clinical sedation scoring systems to evaluate PIC sedation was conducted by Lamas and Lopez-Herce (2010). Whilst only briefly mentioning the methods used in their review, Lamas and LopezHerce (2010) conclude that there is currently no ideal mode to assess sedation for PIC patients.…”
Section: Norwood Usa) and Alaris Auditory Evoked Potentials (Aep) Momentioning
confidence: 99%
“…To date, the most comprehensive review examining the uses and limitations of BIS, MLAEP, and several clinical sedation scoring systems to evaluate PIC sedation was conducted by Lamas and Lopez-Herce (2010). Whilst only briefly mentioning the methods used in their review, Lamas and LopezHerce (2010) conclude that there is currently no ideal mode to assess sedation for PIC patients.…”
Section: Norwood Usa) and Alaris Auditory Evoked Potentials (Aep) Momentioning
confidence: 99%
“…Most of the systematic reviews studying these scales showed that evaluation of pain and sedation in the paediatric ICU patient population is challenging (De Jonghe et al, 2000;Harris et al, 2016;Hartman et al, 2009;Vet et al, 2013). Lamas and López-Herce (2010) indicated that the CS is adequate to evaluate sedation in critically ill children requiring mechanical ventilation. However, no review has used one psychometric analysis scoring system to evaluate all the sedation scales in an integrated and thorough approach.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiating between sedation and analgesia is thus very difficult in young children. (3) However, there is a consensus that sedation and analgesia are essential for the comfort and safety of MV patients. Indeed, sedation and analgesia are proven to reduce MV-associated discomfort, which in turn reduces the use of oxygen, modulates the response to stress intensity, reduces the risk of injury associated with agitation and the displacement of invasive devices, and therefore promotes a patient's safety and facilitates bedside care.…”
mentioning
confidence: 99%
“…To date, no optimal general method to assess sedation in critically ill children is available. (3) Scoring systems, such as the COMFORT system, have only been validated for severely ill MV children, (3) and these systems are useful mainly in children requiring moderate sedation/analgesia. (3) Moreover, little clinical experience is currently available for electroencephalogram (EEG) derived methods, such as the 'bispectral index' (BIS), and these methods have been validated only for anesthetized patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation